Pengaruh Kualitas Pelayanan, Citra Merek Dan Persepsi Harga Kartu Prabayar IM3 Terhadap Kepuasan Pelanggan Di Jakarta Pusat - Adam Yola Mughni; Khalid Azistha Amri; Robby Ferdiansyah; Kumba Digdowiseiso (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine Service Quality, Brand Image and Price Perception of IM3 Prepaid Card on Customer Satisfaction in Central Jakarta. The data analysis technique uses Multiple Linear Regression Analysis and uses the SPSS version 21 program. The results show that there is an influence between Service Quality (X1) on Customer Satisfaction (Y) based on t count 3.769 > t table 1.660 and sig value 0.000 < 0.050. For variable Brand Image (X2) has a positive and significant effect on Customer Satisfaction (Y) based on t count 4.339 > t table 1.660 and sig value 0.000 <0.050. For the price perception variable (X3) on customer satisfaction (Y) based on t count -1.109 > t table 1.660 and sig value 0.027 < 0.050. Partially or simultaneously have a strong influence among the three most significant variables is the variable Brand Image (X2) of 0.000. Among the three variables whose results are significant are the Brand Image (X2) variable with a t-count value of 4.339 > t table 1.660 and a sig value of 0.000 <0.050, and the Service Quality variable (X1) with a t-count value of 3.769 > t-table 1.660 and a sig value of 0.000 < 0.050. The results of this study expect the better the brand image of the IM3 Prepaid Card in the eyes of consumers, the higher customer satisfaction can increase Brand Image (X2) and Service Quality (X1) which can support customer satisfaction. Keywords: Service Quality, Brand Image, Perceived Price, Customer Satisfaction